User Efficiency Model in Usability Engineering for User Interface Design Refinement of Mobile Application - Gladina Desideria; Yoanes Bandung (LPPM ITB, 2020)
Designers are often confronted with challenges or difficulties when designing user interfaces for mobile applications. The information must be clearly delivered to the user and also have an aesthetic appearance and good discoverability. One widely used method for conveying information is directing user attention to a component that is related to his or her task. We propose a recommender system by considering user efficiency in a user attention model. It can give suggestions for designers to improve the appearance of the most efficient component. This recommender system is aimed to help designers in the iteration process of usability engineering, especially to direct user attention to the most efficient component. This system analyzes actual user attention and then refines the user interface based on the energy of each component compared with the baseline energy. Our proposed model successfully increased the efficiency of a mobile learning application from 83.65% to 85.58% and improved discoverability of the most efficient component, thus reducing the task completion time.